Resistome and Genome Analysis of an Extensively Drug-Resistant Klebsiella michiganensis KMIB106: Characterization of a Novel KPC Plasmid pB106-1 and a Novel Cointegrate Plasmid pB106-IMP Harboring blaIMP-4 and blaSHV-12 - Linjing Wang; Haijun Chen; Wanting Liu; Ling Yang; Zhenbo Xu; Dingqiang Chen (MDPI AG, 2023)
Klebsiella michiganensis is a recently emerging human pathogen causing nosocomial infections. This study aimed to characterize the complete genome sequence of a clinical Klebsiella michiganensis strain KMIB106 which exhibited extensive drug-resistance. The whole genome of the strain was sequenced using PacBio RS III systems and Illumina Nextseq 500. Annotation, transposable elements and resistance gene identification were analyzed by RAST, prokka and Plasmid Finder, respectively. According to the results, KMIB106 was resistant to multiple antimicrobials, including carbapenems, but it remained susceptible to aztreonam. The genome of KMIB106 consisted of a single chromosome and three predicted plasmids. Importantly, a novel KPC plasmid pB106-1 was found to carry the array of resistance genes in a highly different order in its variable regions, including mphA, msrE, mphE, ARR-3, addA16, sul1, dfrA27, tetD and fosA3. Plasmid pB106-2 is a typical IncFII plasmid with no resistant gene. Plasmid pB106-IMP consists of the IncN and IncX3 backbones, and two resistance genes, blaIMP-4 and blaSHV-12, were identified. Our study for the first time reported an extensively drug-resistant Klebsiella michiganensis strain recovered from a child with a respiratory infection in Southern China, which carries three mega plasmids, with pB106-1 firstly identified to carry an array of resistance genes in a distinctive order, and pB106-IMP identified as a novel IncN-IncX3 cointegrate plasmid harboring two resistance genes blaIMP-4 and blaSHV-12.